DATA COMPRESSION TECHNIQUE FOR CLOUD STORAGE IN MULTI-USER ENVIRONMENTS - T, Manindra; V, Pradeep K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
In many associations, the cloud storages contain a copy (duplicates) of information. For example, the same file would be spared in various locations by different users; too many documents that are not differentiable may in any case duplication a great part of the same data. This consumes lots of memory in cloud storage. Deduplication is a kind of technique used to eliminate duplicate entries on cloud storage. It helps us to remove the duplicate entries of these additional duplicates, by maintaining only one duplicate of the information and giving ownership rights to the alternate duplicatesÂ with pointers that lead back to the first duplicate. Organizations much of the time utilizes this technique in cloud storage for many applications, yet it can be effectively utilized to free up space in vital situations also. To allow an end-user to have the ownership of the file if the file is already existing and should terminate the uploading process to the cloud storage server